E-learning Managers Training to Design High-tech Electronic Learning Environment - Morze, Nataliia; Buinytska, Oksana (International Journal of Research in E-learning, 2016)
Education today must adequately reflect the needs of the society and be avai-lable throughout life, with an equal access for all people at all levels. The real step in solving these problems consists of creating an information and educational e-environment, using open learning, and providing an open access to educational resources. Organisation and management of the educational process, proper development of IT infrastructure, learning management system, and preparing and creating educational content are still necessary to ensure the quality of the educational information environment. Therefore, there is a need for training that could resolve expressed tasks to organise the educational process to a modern level using an information and educational e-environment available 24*7*365. For this purpose, in the system of e-learning of Borys Grinchenko Kyiv University, an electronic training course “Design and expertise of information and educational e-environment” (available online: http://e-learning.kubg.edu.ua/course/view.php?id=2741) was developed.